2011
DOI: 10.1115/1.4004127
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of NOx Formation From the Lean Premixed Combustion of CH4 Mixed With CO2 and N2

Abstract: This paper describes an experimental and numerical study of the emission of nitrogen oxides (NOJ from the lean premixed (LPM) combustion of gaseous fuel alternatives to typical pipeline natural gas in a high intensity, single-jet, stirred reactor (JSR). In this study. CH4 is mi.xed with varying levels CO2 and Ni. NO^ measurements are taken at a nominal combustion temperature of 1800K. atmospheric pressure, and a reactor residence time of 3 ms. The experimental results show the following trends for A'O, emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…One is the reduction in flame temperature due to the dilution in the reactant [14][15][16][17][18][19], which slows the chemical reaction rate and leads to the reduction in laminar flame speed. This suppression effectively reduces the size of the O/H/OH radical pool [22] and suppresses the formation of NOx. With the presence of CO2 in the reactant, CO2 will compete with O2 for H atom via the reaction of CO 4-OH <-> CO2 -I-H. As a consequence, the reaction rate of most significant chain branching reaction H -I-O2 <-^ OH -h O is suppressed [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…One is the reduction in flame temperature due to the dilution in the reactant [14][15][16][17][18][19], which slows the chemical reaction rate and leads to the reduction in laminar flame speed. This suppression effectively reduces the size of the O/H/OH radical pool [22] and suppresses the formation of NOx. With the presence of CO2 in the reactant, CO2 will compete with O2 for H atom via the reaction of CO 4-OH <-> CO2 -I-H. As a consequence, the reaction rate of most significant chain branching reaction H -I-O2 <-^ OH -h O is suppressed [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…5) δ t along the radial direction. A solid curve calculated using the complementary error function parameterization as C mean = 0 .…”
Section: Mean Flame Brush Locationmentioning
confidence: 98%
“…They found that the reabsorption of emitted radiation due to the presence of CO 2 in fresh gases leads to higher burning velocities and wider extinction limits. Fackler et al [5] suggested that premixed flames diluted with CO 2 produce less NO x due to both a decrease in N 2 concentration and the depletion by CO 2 of radicals participating in NO x formation chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative importance of the different NOx pathways are determined using the procedure first described in reference 42 . This procedure involves identifying of the key reactions for each of the formation pathways and isolating in turn each of the pathways to determine their contribution to NO and NO2 rates of production at each point in the flame.…”
Section: Nox Formation Pathwaysmentioning
confidence: 99%